Pérdida de capacidad de almacenamiento de energía en embalses de generación hidroeléctrica ocasionada por sedimentación (2017)
In Colombia, electrical generation is divided into 69,7% hydroelectric plants, 11,74% natural gas thermal plants, 7,46% carbon thermal plants, 10,4% combustible liquid plants, 0,5% cogeneration plants and 0,12% Eolic plants [1] for a total installed capacity of 15.74 GW. The high dependency of hydraulic resources is directly related to the availability of the previous within Colombia. Unfortunately, this results in undesirable climatic phenomenon's such as ENSO. During times of low hydraulic contribution, it is difficult to guarantee the availability of said supply. The available energy within the reservoirs is needed in its full capacity. Likewise, the sufficiency of supply which is guaranteed and repaid via the reliability charge, requires that the agents and the system provide energy that is firm and dependable. Likewise, in times of high water inflows, the influx of sediments may be high. For this reason, it is considered relevant to carry out studies to take measures on the correct functioning and management of the country's hydroelectric power stations. Based on the previous, it is important to undertake studies that permit the formulation of measures regarding the correct function and management of the hydroelectric centers in Colombia. The results show that the reservoirs studied present a very high loss of energy storage capacity for sediments in the case of Porce III under conditions of high precipitation, being able to obtain loss of 53.66% of the total volume. Under typical climatological conditions it would present losses of 40.25% and under conditions of low rainfall of 26.83% of the total volume of the reservoir. For the case of Guavio, it presents a high sedimentation rate for the critical case of precipitation, reaching a loss of 42.81% over the total volume, 32.07% for the typical case and finally 21.40% for the most favorable case.--Tomado del Formato de Documento de Grado.